(untitled) (Bangladesh Journal of Botany, 2021)
Based on the field experiment of compound soil with volume mixing ratio of soft rock and sand of 1 : 1, 1 : 2, 1 : 5 from 2010 to 2018, the spatio-temporal characteristics and development trend of the mechanical composition of the compound soil with different proportions were studied. The driving factors of the good development of potato growth-compound soil mechanical composition were also explored. Results showed that there was a significant positive correlation between silt-clay mass fraction and cultivation years, the annual variation rates of silt-clay mass fraction were 3.02, 3.90 and 4.11% in 1 : 1, 1 : 2, and 1 : 5 of compound soil. At the initial stage of mixing, clay and silt contents of the compound soil in different proportions were 1 : 1 > 1 : 2 > 1 : 5, and 9 years after planting, clay and silt contents were 1 : 5 > 1 : 2 > 1 : 1, potato growth promoted the development of 1 : 5 compound soil mechanical composition more significantly. The downward migration of silt and clay content in the 0-30 cm surface soil made a relatively dense argic horizon in the 30-40 cm soil layer, which effectively prevented water and fertilizer downward movement and the migration of fine particles in the surface soil. After years of planting, the thickness of the sandy land plow layer has increased to 45 cm, and the three-proportion compound soil mechanical composition developed to a good condition suitable for crop growth, and did not need to be compounded again after many years. Bangladesh J. Bot. 50(3): 865-872, 2021 (September) Special